Surfacial proton conducting CeO2 nanosheets. Issue 6 (15th March 2023) - Paydar, Sara; Zhu, Bin; Shi, Jing; Akbar, Nabeela; Islam, Quazi Arif; Yun, Sining; Muhammad, Akbar; Paydar, Mohammad Hossein; Wu, Yan
Abstract: Proton conducting ceramic fuel cells (PCFCs) have been attracting much more attentions due to is affordable ionic conductivity lower operating temperatures (<600 °C). CeO2 nanosheets expose mainly to the (111) plane exhibit a super proton conductivity of 0.3 S cm −1 and a maximum power density of 948 mWcm −2 at 550 °C. In these two morphologies of CeO2, the difference in Ce 3+ /Ce 4+ ratios and the formation of oxygen vacancies on the surface are mainly responsible for proton transport. Theoretical calculation proves that protons can move more easily on the CeO2 (111) facet with smaller binding energy (0.14 eV) and lower energy barrier for H–O formation (1.7 eV) than on other facets, also superior proton conduction for the nanosheet morphology over the nano-particles. This work has developed a morphological methodology for high proton surface conduction to design highly efficient ionic transport for advanced CFCs and electrochemical devices.